2021
DOI: 10.3389/fcvm.2021.739606
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hepatic Dysfunction After Frozen Elephant Trunk for Type A Aortic Dissection

Abstract: Background: This study was aimed to investigate the incidence, risk factors, and outcomes of patients with postoperative hepatic dysfunction (PHD) after frozen elephant trunk (FET) for type A aortic dissection (TAAD).Method: A retrospective study was performed with 492 patients who underwent FET for TAAD between 2015 and 2019. Independent risk factors for PHD were determined by multivariate mixed-effect logistic analysis with surgeon-specific factor as a random effect.Results: The incidence of PHD was 25.4% (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Kumle et al found that when the CPB time > 180 min, abnormal metabolic function of liver and the destruction of hepatocyte microstructure can occur. [19] Our results show that when the CPB time > 180 min, the risk of severe adverse outcomes in PHD patients increases significantly. Cardiopulmonary bypass is an abnormal physiological circulation in which non-pulsatile blood flow leads to reduced liver perfusion during operation.…”
Section: Discussionmentioning
confidence: 60%
“…Kumle et al found that when the CPB time > 180 min, abnormal metabolic function of liver and the destruction of hepatocyte microstructure can occur. [19] Our results show that when the CPB time > 180 min, the risk of severe adverse outcomes in PHD patients increases significantly. Cardiopulmonary bypass is an abnormal physiological circulation in which non-pulsatile blood flow leads to reduced liver perfusion during operation.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies emphasized that lower-body MHCA duration negatively impacts visceral risk despite the theoretical protective effect of hypothermia [76,77]. In order to reduce lower-body MHCA time and improve distal organ protection, several authors advocated for prompt lower-body reperfusion after completion of the distal anastomosis, using a side branch or a balloon cannula as an endoclamp within the FET [78][79][80]. The Ancona team and other authors have proposed off-pump retrograde vascular stent-graft deployment in distal arch/DTA and the use of a retrograde endoballoon for prompt lower-body reperfusion, allowing TAR during uninterrupted normothermic cerebral and lower-body perfusion [81].…”
Section: Lower-body Perfusionmentioning
confidence: 99%
“…Previous research found that patients with celiac trunk malperfusion before frozen elephant trunk for type A aortic dissection had a trend toward higher early postoperative morality rate. 21…”
Section: Preoperative Moderate/severe Pericardial Effusionmentioning
confidence: 99%